2007 40th Annual Hawaii International Conference on System Sciences (HICSS'07) 2007
DOI: 10.1109/hicss.2007.181
|View full text |Cite
|
Sign up to set email alerts
|

Do Mobile Device Applications Affect Learning?

Abstract: Mobile devices (e.g., PDAs and smartphones) are increasingly emerging as part of daily life, particularly with university students. The City University of Hong Kong has embarked on a long-term program to develop and integrate mobile learning activities into the context of undergraduate courses. This paper reports on the development, introduction and evaluation of a portfolio of collaborative mobile learning applications. Results support convictions that intrinsic and extrinsic motivation to embrace mobile appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 14 publications
(16 reference statements)
2
56
0
1
Order By: Relevance
“…Unlike conventional learning methods that are limited by space and time, mobile learning is available for use anytime and anywhere, while also enhancing individual learning efficiency on the move [23]. Moreover, mobile learning enables the reuse of educational resources and allows individually optimized learning [24].…”
Section: 3mentioning
confidence: 99%
“…Unlike conventional learning methods that are limited by space and time, mobile learning is available for use anytime and anywhere, while also enhancing individual learning efficiency on the move [23]. Moreover, mobile learning enables the reuse of educational resources and allows individually optimized learning [24].…”
Section: 3mentioning
confidence: 99%
“…Kim et al [18] summarize the educational benefits of m-learning as threefold: "(a) mobility, which is associated with the advantage of accessing information anytime, anywhere; (b) information management capacity, which is associated with the digitization of information and electronic-based management; and (c) beaming capability, which allows the sharing of files instantly and in real-time." The pedagogical impact of mobile applications has been evaluated in several different contexts, including language education [19][20][21], business education [8], and employee training programs [3,22]. With respect to science education, the pedagogical impact of mobile applications has been evaluated in primary education [23][24][25][26] and in some disciplines of science in higher education, including physics [17], and medicine [27].…”
Section: Contextmentioning
confidence: 99%
“…With respect to science education, the pedagogical impact of mobile applications has been evaluated in primary education [23][24][25][26] and in some disciplines of science in higher education, including physics [17], and medicine [27]. Findings from these studies report generally positive outcomes, such as: increasing engagement, understanding, and confidence [8]; increasing convenience, flexibility of learning, and engagement in class activities [21]; and facilitating blended learning, which is a learning environment that blends online learning with classroom activities [22]. To our knowledge, there are no studies that describe the pedagogical impact of mobile applications in biochemistry education, although a study by Sears [28] reported that an interactive computer program accessible to undergraduate biochemistry students online (consisting of interactive activities, quizzes, and audiovisual content) increased student retention of material and understanding of structure/function relationships.…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…They allow the access to remote learning resources, educational games and quizzes. Additionally, they allow for communication among learners to share educational information [4]. Mobile learning is accomplished by the use of mobile devices such PDAs, Smartphones, Ipads and tablets.…”
Section: Introductionmentioning
confidence: 99%